Rodent models for Alzheimer's disease drug discovery. (July 2015) - Puzzo, Daniela; Gulisano, Walter; Palmeri, Agostino; Arancio, Ottavio
<x xml:space="preserve">Abstract</x> Introduction: Alzheimer's disease (AD) is a neurodegenerative disorder characterized by memory loss and personality changes, leading to dementia. Histopathological hallmarks are represented by aggregates of beta-amyloid peptide (Aβ) in senile plaques and deposition of hyperphosphorylated tau protein in neurofibrillary tangles in the brain. Rare forms of early onset familial Alzheimer's disease are due to gene mutations. This has prompted researchers to develop genetically modified animals that could recapitulate the main features of the disease. The use of these models is complemented by non-genetically modified animals. Areas covered: This review summarizes the characteristics of the most used transgenic (Tg) and non-Tg models of AD. The authors have focused on models mainly used in their laboratories including amyloid precursor protein (APP) Tg2576, APP/presenilin 1, 3xAD, single h-Tau, non-Tg mice treated with acute injections of Aβ or tau, and models of physiological aging. Expert opinion: Animal models of disease might be very useful for studying the pathophysiology of the disease and for testing new therapeutics in preclinical studies but they do not reproduce the entire clinical features of human AD. When selecting a model, researchers should consider the various factors that might influence the phenotype. They should also consider the timing of testing/treating animals since the age at which each model develops certain aspects of the AD pathology varies.